Rebound pain after regional anesthesia in the ambulatory patient - Lavand'homme, Patricia (Current opinion in anaesthesiology, 2018)
Regional anesthesia is popular in ambulatory setting allowing safe and fast recovery. The problem of 'rebound pain', that is very severe pain when peripheral nerve block (PNB) wears off represents a clinically relevant problem and a cause of increased healthcare resource utilization. This review tries to make the point on a not so rare, unwanted and often neglected side effect of PNB. The major finding is the lack of large prospective studies. Incidence of rebound pain is unknown but could reach 40% of patients at PNB resolution. To date, pathophysiological mechanisms remain debated: mechanical and chemical (proinflammatory effect of local anesthetics) nerve insult caused by PNB in predisposed patients (with severe preoperative pain, younger patients). Effective preventive strategies also are missing (e.g. role of analgesic adjuvants in PNB). Long-term consequences in term of functional recovery and persistent pain have not been demonstrated. Interview of patients has underlined the need of information and education about PNB and postoperative analgesia. Patients' report of excruciating pain and major distress when PNB wears off questions the quality of current anesthesia practice in ambulatory setting. Rebound pain unanswered questions are challenging in the area of perioperative medicine.